Monitoring of Climate Changes and the State of Natural Complexes of the Cheremsky Nature Reserve - Fedoniuk, V.; Zhadko, O.; Fedoniuk, M.; Vovk, Oleksandr P.; Ivantsiv, V. (European Association of Geoscientists & Engineers, 2023)
In recent decades, global climate changes have resulted in a range of regional climatic processes and phenomena, exerting significant impacts on the natural complexes within nature conservation areas, protected objects, and elements of the ecological network. The study of these effects is highly pertinent to the territories and natural systems encompassed by the Cheremsky Nature Reserve, a particularly valuable nature conservation complex in Northwestern Polissya. Our analysis was based on meteorological data from the nearest weather station, complemented by remote sensing techniques examining vegetation and water indices over the 5-year period. This examination revealed several notable deviations from climatic norms, including: an increase in annual and maximum air temperatures by 2.0°C and minimum temperatures by 1.0-1.5°C, an increase in annual precipitation by 5-6%, a drastic reduction in snow cover duration by 2-2.5 times, a decrease in the number of days with precipitation by 10-17%, a substantial increase in the number of days with thunderstorms. These findings suggest a negative impact on natural complexes, primarily due to an increase in evaporation from the active surface and a corresponding decrease in the humidity coefficient by 20-25%. Additionally, our study revealed the interrelation between vegetation processes and the dynamics of climatic indicators.